Defect engineering in organic semiconductor based metal-dielectric photonic crystals - Khadga S. Thakuri; Thomas Cleary; David Allemeier; Taisei Kimura; Naoya Aizawa; Ken-ichi Nakayama; Akito Masuhara; Matthew S. White (Scientific Reports, 2024)
Abstract We investigate the band structure of metal-dielectric photonic crystals comprising stacked organic semiconductor microcavities with silver metal mirrors incorporating crystal defects: individual unit cells with aperiodic dimensionality. Both transfer matrix simulation and experimental verification are performed to investigate the impact on the photonic band structure as a single cavity is varied in size. The resulting mid-gap defect states are shown to hybridize with a photonic band at certain resonant dimensions. The resonance of the defect cavity affects the transmittance of light through the device, disrupting or enhancing the coupling between otherwise resonant cavities. We outline potential applications for defect engineering of these devices through controlled manipulation of the transmission spectrum.